Полевой определитель пингвинов (Spheniscidae, Natantes) - Meйснер, Э.Э.; Головерси, Э.В. (Вестник зоологии, 1972)
Penguins is an isolated group of specifically organized birds inhabiting the soutl hemisphere from tropical latitudes to the Antarctica. They live an aguatic life as a result of which the structure of their body changed and the ability to fly disappeared. They feed on fish, crustaceans, cephalopods. 17 species of penguins are known. They differ well from each other in external features. These differences are accepted as a basis of the suggested determination table.